Hepatitis E Virus in Manure and Its Removal by Psychrophilic anaerobic Biodigestion in Intensive Production Farms, Santa Catarina, Brazil, 2018–2019 - Doris Sobral Marques Souza; Deisi Cristine Tápparo; Paula Rogovski; Rafael Dorighello Cadamuro; Estêvão Brasiliense de Souza; Raphael da Silva; Roberto Degenhardt; Juliano De Dea Lindner; Aline Viancelli; William Michelon; Airton Kunz; Helen Treichel; et al. (Microorganisms, 2020)
Hepatitis E virus (HEV) is an important enteric agent that can circulate in swine; it is excreted in manure, and of zoonotic interest. The present study investigated, by RT-qPCR, the circulation of HEV in swine manure from different types of pig farms (maternity, nursery, and grow-finish farms) in Santa Catarina State, the major pig production area of Brazil, and also evaluated the HEV removal efficiency of psychrophilic anaerobic biodigesters (PABs). While HEV was consistently detected in manure from grow-finish pig farms (>4 log HEV genome copies (GC) L−1), the virus was not detected in manure from maternity and nursery farms. These findings suggest a potential high biosafety status during primary-swine production, with a subsequent contamination in grow-finish production. The anaerobic biodigestion process reduced more than 2 log10 HEV GC in the processed swine manure. However, the virus concentration in final effluent remained high, with an average value of 3.85 log10 HEV GC L−1. Consequently, our results demonstrate that PABs can be a robust tool for effective inactivation of HEV, while reinforcing the need for sanitary surveillance and legislation of swine manure-derived biofertilizers, to avoid the spread of zoonotic enteric pathogens such as HEV.